PENANAMAN NILAI-NILAI KARAKTER ISLAMI MELALUI KEGIATAN EKSTRAKULIKULER AL-BANJARI DI MA AL-IHSAN KALIKEJAMBON TEMBELANG-JOMBANG - Lestari, Retno Dwi; Ahdi, Wafiyul; Rohmah, Hidayatur (Universitas KH. A. Wahab Hasbullah, 2021)
This device is motivated by a phenomenon that is interesting to study and research in relation to Islamic character. Some students have Islamic characters while some other students have non-Islamic characters. Students with Islamic characters are always pleasing to everyone's eyes. Discipline, confident, diligent, responsible, respect for friends, respect for teachers or elders, strong religion, friendly and tolerance are inherent in their every behavior. It is different from students who has a non-Islamic character, almost everyone dislikes him. Students with non-Islamic characters tend to be undisciplined, lazy, insecure, irresponsible, like to annoy friends, fight against teachers, selfish and less Islamic. In this case the researcher trying to find out how to instill the values ​​of Islamic character education in al-banjari extracurricular activities at MA Al-Ihsan Kalikejambon Tembelang Jombang.